A study on utilization of zeolite as partial replacement to cement for M40 grade concrete - Sandeep Reddy, G.; Ramu, Penki; Venkata Aneesh Mohan, M. (International Journal of Engineering and Technology, 2019)
Cement plays an essential role for the concrete production. Production of cement emits a greenhouse gas CO2 during the calcination of limestone. CO2 emissions can be reduced by using supplementary cementitious material (SCM) as replacement to cement in concrete. Use of supplementary cementitious material also improves the performance of concrete. One such naturally available supplementary cementitious material, natural zeolite was been used in the present investigation. In the present experimental investigation, 15% of cement content (by weight) in standard concrete of grade M40 is replaced with zeolite. The important parameters that influence the strength of concrete such as water-binder ratio (0.37, 0.38, 0.39, and 0.40) and binder content (440, 450, 460, and 470 kg/m3) are considered for the investigation. Total 16 mixes were cast and tested for compressive strength as per IS 516. The compressive strength of concrete was tested on a cube of 150 X 150 X 150 mm size at the age of 7 and 28 days. From the obtained experimental results, water-binder ratio of 0.37 and binder content 440 kgs per cubic meter (85% cement + 15% zeolite) were found enough for the production of M40 grade concrete.Â Â